Meningkatkan Hasil Belajar Siswa Pada Pelajaran Matematika Di Kelas VIII-2 Melalui Strategi Pembelajaran Mean And Analysis Di SMP Negeri 1 Tanjung Morawa Tahun Pelajaran 2019/2020 - Duena Maritha Sihotang (Ability: Journal of Education and Social Analysis, 2023)
The purpose of this research is to: (1). Improving student learning outcomes, (2). Increase student learning activities. (3). Increase student understanding and learning using the Mean and Analysis learning strategy. The method used in this research is the Classroom Action Research Method using 2 cycles. The subjects of this study were 33 class VIII-2 students of SMP Negeri 1 Tanjung Morawa. Because the number of subjects was under 100 people, all subjects were sampled in this study. The instruments used to obtain data are tests, questionnaires and observations. The data analysis technique used is the assessment method, namely: the data obtained is evaluated based on student learning outcomes. Evaluation of student learning outcomes is given a range of values ??from 0 – 100. Then the data is calculated from the average student score, the percentage of students who have completed and the percentage of students who have not completed meeting the minimum completeness criteria. (1). The results of this study indicate that there is an increase in learning outcomes by applying the Mean and Analysis learning strategy with the following results: (1) there is an increase in the average student learning outcomes, where in the initial test the average student learning outcomes is 49.39%, in the second cycle I increased to 62.73% then in cycle II it increased again to 72.42%, there was an increase in the number of students who completed, where in the initial test the number of students who passed was only 0%, increased to 48.48% in cycle I then increased again to 87.88% in cycle II, there was a decrease in the number of students who did not complete, where in the initial test the number of students who did not complete reached 100%, in cycle I it became 51.52% then in cycle II it decreased again to 12.12% with In other words, only 4 students scored 60 and the rest (29) students scored 70 and above 70.